Persepsi Guru PAI Terhadap Penggunaan Canva sebagai Media Pembelajaran di SDIT Fitrah Insani 2 - Dewi, Ratna; Fathony, Aditya Achmad; Gifari, Muhamad Kosim; Gunadi, Rustian Akbar (IIQ An Nur Yogyakarta, 2025)
This study aims to analyze the perceptions of Islamic Education / Pendidikan Agama Islam (PAI) teachers at Fitrah Insani 2 Integrated Islamic Elementary School (SDIT) regarding the use of the Canva application as a learning medium. The background of this study is based on the importance of innovative learning media that suit the characteristics of elementary school students in adapting to the development of digital technology. The study employed a descriptive quantitative approach with a questionnaire as the instrument, distributed to all PAI teachers. The results showed that most teachers held a positive view of Canva. Specifically, 89.6% of teachers stated that Canva makes it easier for teachers to create engaging, efficient, and student-appropriate learning materials. Teachers also reported feeling more confident in their teaching and that Canva helps in conveying abstract concepts through engaging visuals. In conclusion, the Canva application has the potential to be an effective tool for enhancing the quality of PAI learning media at SDIT.